Dissociations in routine behaviour across patients and everyday tasks. - Forde, E; Humphreys, G (2002)
We present a single case study of a patient, FK, who was severely impaired on routine, everyday tasks, such as preparing a cup of tea. We used the action coding system developed by Schwartz et al. to provide quantitative and qualitative measures of his performance in a number of experimental manipulations. In section A, we established FK's baseline performance on a range of tasks with (a) task-congruent objects only and (b) task-congruent objects and semantic distracters. In section B, we aimed to facilitate FK's performance by (a) giving him a pictorial representation of the goal, (b) giving him a set of written commands to follow, (c) giving him one command at a time, (d) demonstrating how the task should be performed and (e) dividing the task into smaller subgoals. We compared FK's performance with another patient, HG, to establish if there are qualitative differences between patients with 'action disorganization syndrome'. In section C, we aimed to hinder FK's performance by interrupting his execution of routine tasks. By comparing the factors that facilitated and impaired FK's performance in sections B and C, we hoped to isolate the key cognitive processes required to generate and control routine behaviour. In section D, we investigated how task demands impact on our ability to complete different everyday activities. The results of these experiments have important clinical implications for rehabilitation programmes for patients with action disorganization syndrome and can also help to distinguish between contemporary theoretical accounts of routine behaviour. In particular, we propose that patients who can be classified under the umbrella term of 'action disorganization syndrome' do not all have a reduction to 'non-specific cognitive resources' but can have qualitatively different impairments to a specialized action production system.